If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -2 + 3x = -8 Reorder the terms: -2 + 3x + 3x = -8 Combine like terms: 3x + 3x = 6x -2 + 6x = -8 Solving -2 + 6x = -8 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 6x = -8 + 2 Combine like terms: -2 + 2 = 0 0 + 6x = -8 + 2 6x = -8 + 2 Combine like terms: -8 + 2 = -6 6x = -6 Divide each side by '6'. x = -1 Simplifying x = -1
| 11p=-22 | | 8+6x=-64 | | Y=(7x+3)(2x-1) | | 9x+21+8y= | | 9=13+a | | 2.3a+4=15.5 | | 15x^2-8x-8=0 | | 28+20=35+13 | | 0.16x+3=3.48 | | -17=x-20 | | M(a)=3a-7 | | 30=2/5v | | 13=n+18 | | 7y=14/9 | | 5xcan(x^3+1)=2x(x^2+2) | | n^2-n-60=0 | | 2x-2x+3y=12-2x | | 6x-9=5x+5 | | 25=18+a | | y-49.763=0 | | x^2+28x=19 | | 6b^2-13b-8=0 | | 32-3x=16+5x | | 12.5=t+3.55 | | -sin(pi)x=0 | | -sin(pix)=0 | | x^2+6+11=0 | | H+8=10 | | 2x^3=-x^2+18x+9 | | 0.6x+1=19 | | n^2-62=0 | | 2x^4-28x^2+96= |